Ethical and Policy Concerns pertaining to Rice Landraces in Asia - Gupta, Abhik (Bangladesh Journal of Bioethics, 2012)
Domestication of rice (Oryza sativa L.) from the wild species O. rufipogon and O. nivara by Neolithic Asian farmers more than 10,000 years ago represents one of the most important events in human history, as this crop is the major staple food of over one-third of the world’s population, meeting around 20 % of the global calorie intake. The Asian rice, O. sativa, which is grown worldwide, has three major “variety groups” or subspecies: indica varieties of the Indian subcontinent; tropical japonica or javanica varieties very common in southeast Asia and southern China; and temperate japonica varieties predominantly cultivated in northeastern Asia. Furthermore, cultivation and farmer selection over a long period of time have given rise to over 120,000 varieties or farmer’s landraces of rice. These include glutinous and non-glutinous landraces, aromatic landraces; those taking different times to mature; with different levels of tolerance to abiotic stresses like cold, drought, submergence and salinity; and even differing in their resistance to pests and diseases. However, a few hundred “high-yielding” “improved” varieties have largely replaced these traditional landraces, with the latter finding their place of preservation in the rice germplasm banks. While it is true that various genes of the traditional landraces have been incorporated into many modern varieties, questions arise as to the ethical propriety of banishing ‘live’ and ‘flourishing’ life forms that are also integrally linked to the culture of many communities, to a ‘synthetic, and overtly utilitarian existence. The present paper aims to discuss these issues in the light of ethical principles as well as policies pertaining to traditional knowledge and practices. DOI: http://dx.doi.org/10.3329/bioethics.v2i1.9811 Bangladesh Journal of Bioethics 2011; 2(1): 7-12